2012
DOI: 10.1097/bot.0b013e318228b7ad
|View full text |Cite
|
Sign up to set email alerts
|

All-Terrain Vehicle-Related Orthopaedic Trauma in North Central West Virginia

Abstract: This trauma center is in a unique position to highlight a national problem. Over half (52%) of the patients had an orthopaedic injury defined as a fracture or dislocation. Before measures can be implemented to effect change, we must first be aware of the exact nature and spectrum of injuries associated with ATV use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“… 12 Dietz et al (2012), reported that the percentage of riders under age 18 in West Virginia wearing helmets actually decreased from 67% to 55% after the enactment of a helmet law there. 15 Our findings further support previous studies reporting abysmally low helmet use rates among ATV riders ranging from 5% to 50%. 8 , 9 , 12 , 13 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 12 Dietz et al (2012), reported that the percentage of riders under age 18 in West Virginia wearing helmets actually decreased from 67% to 55% after the enactment of a helmet law there. 15 Our findings further support previous studies reporting abysmally low helmet use rates among ATV riders ranging from 5% to 50%. 8 , 9 , 12 , 13 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Discussionsupporting
confidence: 92%
“…Proper helmet use is estimated to reduce the risk of head injury by 64% and the risk of death by 42%. 12 , 13 , 14 , 15 , 16 Helkamp in 2001 showed a two-fold increase in ATV-related mortalities in states without helmet laws. 17 Despite this evidence in support of helmet use, lack of acceptance and highly variable, poorly enforced policy intervention still results in low helmet use among ATV riders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other studies in which no more than 34% of subjects wore helmets, 6,7,[13][14][15] we found that 38.6% of patients were confirmed to be wearing a helmet at the time of their injury. Although legislation is believed to be a contributing factor to helmet use, our results suggest that there was no significant change in helmet use among injured riders following the introduction of more stringent legislation.…”
Section: Discussionsupporting
confidence: 90%
“…The ineffectiveness of legislation alone has been found in other studies. 6,7,[13][14][15][16][17] There could be several reasons for this finding.…”
Section: Discussionmentioning
confidence: 99%